Evidenciação dos riscos de mercado pelas empresas do novo mercado da BM&FBovespa - Tomé, Francisco Werbson Campos (2012)
The overall objective of this study is to investigate the degree of compliance with disclosure requirements relating to market risks defined in CVM Instruction 480/2009 by publicly traded companies listed on the BM&FBovespa. Considering the informational efficiency of the U.S. market as well as the legal model of that country (TORRES; BONOMO; FERNANDES, 2002; BONE; RIBEIRO, 2002) and the result of research conducted by Goulart (2003) (identifying the disclosure that the bank in the domestic market, despite showing indicators developments in the area of market risks, shows an incipient level of transparency compared with the practices of dissemination of the international financial institutions), is assumed as the research hypotheses: (i) the level of disclosure of market risks companies issuing ADR is statistically different from the companies non issuing ADRs, and (ii) the level of disclosure of market risks of financial firms is statistically different from non-financial corporations. The study sample consists of 125 publicly traded companies traded on BM&FBovespa, listed on the "New Market" segment of the date of 12.31.2011. The selected companies were classified into issuing and non issuing ADR. In addition, companies were also separated into financial and non financial sector classification as the BM&FBovespa. Data analysis was performed by combining the two methods in the following order: (1) content analysis to identify items of market risks as evidenced by the firms in the reference forms disclosed by companies in 2011, and (2) Test Medium, for comparative analysis of disclosure of market risks between the groups mentioned. The analysis was performed in a segmented way, as evidenced items contained in the form of reference: 5.1-item description of market risk that the issuer is exposed (mandatory information); 5.2-political management of market risks taken by issuer, its objectives, strategies and instruments; item 5.3-significant changes in key market risks to which the issuer is exposed, and item 5.4, relevant information (mandatory). The results indicate that the average level of disclosure of market risks of the companies surveyed was 86.60%. The descriptive analysis also showed that firms in the sample had a homogeneous level of disclosure. Through the statistical test of mean difference, it was found that no significant difference between the means of dissemination of companies as the issue of ADR and depending on the participation in the financial sector.